2004
DOI: 10.1071/bt03108
|View full text |Cite
|
Sign up to set email alerts
|

The influence of fire and rainfall upon seedling recruitment in sand-mass (wallum) heathland of north-eastern New South Wales

Abstract: Wallum heathland is extensive on coastal sand masses in north-eastern New South Wales and south-eastern Queensland. Here the climate is subtropical, although monthly rainfall is highly variable and unreliable. We examined the influence of fire and rainfall on seedling recruitment in bradysporous dry-heathland [Banksia aemula R.Br., Melaleuca nodosa (Sol. ex Gaertn.) Sm.] and wet-heathland [Banksia oblongifolia Cav., B.�ericifolia L.f. subsp. macrantha (A.S.George) A.S.George, Leptospermum liversidgei R.T.Baker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 83 publications
1
4
0
Order By: Relevance
“…9.3-9.4 m AHD) where the topsoil was sandier. The association of Melaleuca nodosa with a shallow water table is consistent with Griffith et al (2004) . Substantial rainfall (> 600 mm over a four month period) was shown to replenish the water table in the current study by about 1 m. Recharge of the groundwater after large rainfall events (> 250 mm in a month) could take up to a month when prior conditions had been relatively dry.…”
Section: Vegetation Soils and Water Table Depthsupporting
confidence: 66%
“…9.3-9.4 m AHD) where the topsoil was sandier. The association of Melaleuca nodosa with a shallow water table is consistent with Griffith et al (2004) . Substantial rainfall (> 600 mm over a four month period) was shown to replenish the water table in the current study by about 1 m. Recharge of the groundwater after large rainfall events (> 250 mm in a month) could take up to a month when prior conditions had been relatively dry.…”
Section: Vegetation Soils and Water Table Depthsupporting
confidence: 66%
“…Heaths in Australia occur on a variety of substrates from very dry and barren rocky outcrops to moist and wet plains, soaks and swamp, and observers and botanists have historically described heaths as ‘wet’, ‘dry’ and in some cases ‘not so wet’ (Griffith et al., 2004; Harrold, 1994; Specht & Specht, 1989). Dry heaths in various sites across south‐eastern Australia were previously found to contain twice the alpha diversity (SR) of wet heaths (Specht & Specht, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to expectations, this study found wet sites on the Sunshine Coast to contain a similar diversity to dry sites, with moist sites significantly higher in diversity than wet or dry sites. Likewise, the ‘intermediate’ dry heaths of coastal New South Wales were observed to have higher diversity and to display ecotonal or transitional characteristics between wet and dry heath (Griffith et al., 2004). The moist sites on the Sunshine Coast display an overlap of plants suited to both dry and wet places as documented in the species composition patterns of this study and in the phylogeny.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations